COGNITIVE BIAS AND BEGINNER INVESTORS - Trisilo, Rismanto Gatot; Christanti, Paramita Lea; Sulistyowatie, Syska Lady (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
Forex investment is one of the investment instruments that is popular among the people of Indonesia. However, forex investment also has high risks, so it is important for investors to understand the factors that can affect their investment decisions, this study aims to test the influence of recency bias and familiarity bias on the decision-making of beginner investors in forex investment, this study uses a quantitative method with a survey design and the population of this study is students of the management study program UNIWDHA Klaten who have received learning about the stock market and forex and becoming a beginner investor, the research sample amounted to 47 people. From the results of this study, recency bias and familiarity bias are equally significant in influencing the decisions of novice investors, although recency bias has a greater influence than familiarity bias, from this result hopefully it can help in making investment decisions in the future